Determinants of~market outlet choices by~smallholder mango farmers in~Aleta Chuko District, Sidama Region, Ethiopia: A multivariate probit approach - Tibebu Legesse; Aneteneh Ashebir; Zerhun Ganewo; Abera Alemu; Andachew Samuel (Journal of Innovation and Entrepreneurship, 2024)
Selecting appropriate market outlets offer the opportunity for farmers to capture a bigger share of the price paid by final consumers. However, smallholder farmers in developing countries are still confronted with myriad challenges regarding selecting profitable market outlets. Thus, the main objective of this study was to analyze determinants of market outlet choices by smallholder mango farmers in Aleta Chuko District, Sidama Region, Ethiopia. The study's representative 391 sample mango producers were selected using a multi-stage sample selection technique and a cross-sectional research approach. Descriptive statistics and the multivariate probit model were used to analyze the data. The result of the study showed that the probability of mango producers to choose consumer, collector, and retailer and wholesaler market outlets was 38%, 39.4%, 41% and 25%, respectively. This shows that retailer was the most likely chosen market outlet while wholesaler was the less likely chosen market outlet. The joint probability of farmers to choose the four market outlets is (0.042%) lower than the likely of not choosing four market outlets (23.21%). The result of the multivariate probit model showed that the sex of the household head, age of the household head, educational level of the household head, the quantity of mangoes produced, size of the land allocated for mango production, use of market information, credit access, livestock holdings, and distance to the nearest market were all statistically and significantly influencing factors in the market outlet choice behavior of mango producers. Based on the results of this study, the government and other concerned organizations should take action to improve the efficient marketing of mango producers in all outlets by providing market information, expanding and following up on extension services, increasing credit access, and building roads and other marketing infrastructure in the study area.
Keywords: 650; Mango producers; Market outlet; Multivariate probit model